Bunny and Clyde - McDonald, Megan (Candlewick Press, 2024)
These buddies, a rabbit and a chipmunk, are sick and tired of being good. They want to know what it's like to be baddies, and they want thrills and excitement, but they're going to need some experience making mischief. Next thing you know, they're shelving books in un-alphabetical order and borrowing markers without asking, and that's just the warm-up. In no time they'll be hardened criminals.